Corporate Governance and Performance of Commercial Banks in Nepal (SNPRC Journal, 2023)
The purpose of this study was to examine the effect of corporate governance on performance of commercial banks in. It also examined the corporate governance practices of commercial banks. The study followed quantitative approach and descriptive research design. Multiple regression analysis was used to explore the causal relationship between corporate governance and financial performance of commercial banks. The study revealed a positive relationship of number of board meeting and foreign ownership and bank performance which shows higher the board meeting, foreign investment higher would be the bank performance. However, there was negative relationship of board size and capital adequacy ratio with bank performance indicating higher the board size, capital adequacy ratio would lead lower bank performance. Practices of corporate governance system of financial sector in Nepal is still infant stage however joint venture banks practices are more harmonizing rather than government banks and other banks.